Випробування технології піроліза рідких палив для систем живлення транспортних енергоустановок - Sudnik V.K.; Melnichuk L.P.; Orlov V.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2002)
The results of technology test of fuel hydrolysis for feed systems of transport electrical equipment are considered. Investigations of gasification depending on process parameters are carried out. Following the results of experimental data processing, the empirical dependence for gasoline conversion modes calculation is deduced. The rating of hydrolysis product motor performance is carried out.